Key to the Ophiodes (Squamata: Sauria: Diploglossidae) of Paraguay with the description of a new species - Cacciali, Pier; Scott, Norman J. (Zootaxa, 2015)
Ophiodes is a South American genus of legless diploglossid lizards. Four species have been formally described: O. intermedius, O. vertebralis, O. striatus, and O. fragilis; three additional species were described but not officially named in an unpublished dissertation. These species are referred to as Ophiodes sp. “1”, Ophiodes sp. “2”, and Ophiodes sp. “3”. We recognize five species of Ophiodes in Paraguay, one widespread (O. intermedius) and four known from only one or two localities (O. fragilis, O. striatus, O. sp. “3”, and an undescribed species, described herein). The new species described represents the fifth Paraguayan species and the eighth member of the genus. It is distinguished by a combination of the following characters: a high number of middorsal scales between occipital and cloacal opening (>165), 29 scale rows around midbody, the posterior limbs 4 scales long, and vertical black bars on the face absent.